Kontribusi Maqāshid al-Syarī‘ah dalam Pengembangan Bioetika Islam: The Contribution of Maqāshid al-Syarī‘ah in the Development of Islamic Bioethics - Muhamad Wildan Arif Amrulloh; Zaman, Mehdar Badrus (Center of Islamic and Occidental Studies, 2024)
Advancements in medicine and biology have brought significant changes in medical practices, giving rise to new ethical issues such as surrogate motherhood and egg or sperm donation. In such cases, bioethics is essential. However, the prevailing bioethics is predominantly Western, diverging from Islamic ethical principles, thus potentially leading to different ethical conclusions. Hence, Islamic bioethics needs to be introduced and developed. One instrument used in this development is maqāshid al-Syarī’ah. This article aims to examine the contribution of maqasid al-shariah in the development of Islamic bioethics. Employing a literature review method, the article explores literature on Islamic bioethics and maqāshid al-Syarī’ah. The study's findings suggest that maqāshid can bridge Islamic principles with existing realities, enabling Islamic bioethics to address contemporary bioethical issues without compromising Islamic values.